Complicated femoral aneurysms - Larre Borges, Uruguay; Filgueira, José L; Rubio, Roberto (Cirugía del Uruguay, 2021)
Authors presents two observations of complicated femoral aneurisms, with rupture in one case, and obstruction in the other. Both were succesfully treated.